PERUBAHAN SOSIAL KOMUNITAS SUKU ARFAK KABUPATEN PEGUNUNGAN ARFAK PAPUA BARAT - Therresse Nofianti (Syarif Hidayatullah State Islamic University Jakarta, 2019)
Changes in society related to changes in social values, norms, patterns of organizational behavior, the composition of social institutions, social interaction. Arfak Mountains Regency formed since 2012 through Law Number 24 of 2012 is the main district which was later divided into South Manokwari Regency and Arfak Mountains. The Arfak mountain community is referred to as the large Arfak tribe because it consists of several sub tribes namely Hatam, Moile, Sough and Meyah. This paper aims to provide an overview and information about social changes that occur in the Arfak tribal community in the Arfak Mountains Regency, West Papua Province. The method used is a literature review of various reports or scientific studies related to the context of social and cultural change in the Arfak tribal community. These materials were analyzed using Herbert Spencer's theories of social change, Talcot Parson, Kingsley Davis's modern theory (Demographic Transition). The results obtained show that social changes in the Arfak tribe in the Arfak Mountains District occur due to changes in the composition of the population, the existence of the Papua Special Autonomy Policy, the inclusion of new innovations, easier transportation, empowerment programs, changes in customary institutions and values and norms that have an impact positive and negative on people's lives.